Managing learning organization in industry 4.0 : proceedings of the International Seminar and Conference on Learning Organization (ISCLO 2019), Bandung, Indonesia, October 9-10, 2019 /: proceedings of the International Seminar and Conference on Learning Organization (ISCLO 2019), Bandung, Indonesia, October 9-10, 2019. (2020) - Unknown
No abstract available